2020
DOI: 10.15561/26649837.2021.0301
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plyometric training on performance levels of the shot put technique and its related motor abilities

Abstract: Background and Study Aim: The aim of this research is to evaluate the effects of plyometric training on the shot put technique. It was oriented to improve the basics for the development of power related-indicators such as power (explosive force), acceleration speed, and strength endurance. Material and Methods. The study sample included 220 male students, aged 16 years ± 6 months from Fehmi Lladrovci High School, Glogoc municipality, Republic of Kosovo from the 2019/2020 academic year. The experimental g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Ramachandran et al, (2021) examined the effects of plyometric training on balance performance and stated that balance performance improved. In the study examining the effect of plyometric training on the performance levels of shot put technique and related motor skills, it was observed that the mean values of the flamingo balance test (p<0.05) pre and post test (tests within subjects) were statistically different from the measurements over time (Thaqi et al, 2021). In line with the results obtained, it is seen that plyometric training methods in addition to classical football training improve the jumping performance more.…”
Section: Discussionsupporting
confidence: 55%
“…Ramachandran et al, (2021) examined the effects of plyometric training on balance performance and stated that balance performance improved. In the study examining the effect of plyometric training on the performance levels of shot put technique and related motor skills, it was observed that the mean values of the flamingo balance test (p<0.05) pre and post test (tests within subjects) were statistically different from the measurements over time (Thaqi et al, 2021). In line with the results obtained, it is seen that plyometric training methods in addition to classical football training improve the jumping performance more.…”
Section: Discussionsupporting
confidence: 55%
“…Supporting research in this study was conducted by Thaqi et al, (2021), with the title the effect of plyometric training on shot put ability, and the results obtained were significant. Based on the results of the study, there were similarities, namely using shot put abilities for the dependent variable, while for the independent variables there were differences, namely using plyometric exercises, while the researchers used standing bench press exercises, but the results of data analysis showed that the exercises were carried out to improve the ability to shoot.…”
Section: Resultsmentioning
confidence: 82%
“…Ten studies [ 26 , 40 , 83 , 85 , 98 , 99 , 103 , 105 , 107 , 108 ] examined non-athletes (including resistance-trained participants and physical education students). Other studies examined athletes from different sports such as handball (n = 5) [ 86 , 88 , 90 , 91 , 96 ], basketball [ 28 , 82 , 101 ], baseball [ 41 , 89 , 104 ], tennis [ 93 , 94 , 110 ], volleyball [ 20 , 21 , 106 ] (n = 3 for each sport), cricket [ 84 , 102 ] (n = 2), golf [ 87 ], karate [ 97 ], rugby [ 100 ], softball [ 92 ], and table tennis [ 95 ] (n = 1 for each sport).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding participants' sex, 6 studies reported a mixed sample of male and females (n = 287 [20.3% of total participants]), 13 groups involved females only (n = 216 [15.3% of total participants]), 44 groups involved males (n = 821 [58.2% of total participants]), and 6 groups involved unspecified participants' sex (n = 88 [6.2% of total participants]) (Table 3 ). All except six studies [ 21 , 94 , 97 , 105 , 109 , 110 ] recruited experimental and control groups from the same sample through randomization procedures (e.g., groups with similar [probability] training-competition level, age, sport). According to one study [ 94 ], pre-tests were employed to regulate the initial status of players.…”
Section: Resultsmentioning
confidence: 99%